Kerfoot, C & Hyltenstam, K (eds.). 2017. Entangled discourses: South-North orders of visibility. Oxon: Routledge. - Catherine Manathunga (University of Johannesburg, 2018)
Catherine Manathunga reviews Caroline Kerfoot and Kenneth Hyltenstam's Entangled discourses: South-North orders of visibility which "explores the multiple entanglements of Northern and Southern linguistic, cultural and knowledge systems". As a historian, Manathunga believes this edited collection offers "fresh frameworks for a wide variety of disciplinary experts seeking to grapple with the complexities of contemporary globalisation, capitalism, colonialism and imperialism". How to cite this book review: MANATHUNGA, Catherine. Book review: Kerfoot, C & Hyltenstam, K (eds.) 2017. Entangled discourses: South-North orders of visibility. Oxon: Routledge. Scholarship of Teaching and Learning in the South v. 2, n. 2, p. 90-91, Sept. 2018. Available at: http://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=82&path%5B%5D=27 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/